Advances in hydrophilic metal–organic frameworks for N-linked glycopeptide enrichment - Li, Siqi; Wei, Yuanhua; Wang, Ya; Liang, Haoran (Frontiers in Chemistry, 2022)
The comprehensive profiling of glycoproteins is of great significance for the timely clinical diagnosis and therapy. However, inherent obstacles hamper their direct analysis from biological samples, and specific enrichment prior to analysis is indispensable. Among the various approaches for glycopeptide enrichment, hydrophilic interaction liquid chromatography (HILIC) has attracted special focus, especially for the development of novel hydrophilic materials, which is the key of HILIC. Metal–organic frameworks (MOFs) are a type of porous materials constructed from the self-assembly of metal and organic linkers. Advantages such as high surface area, flexible pore size, and easy modification render hydrophilic MOFs as ideal candidates for HILIC, which has inspired many studies over the past years. In this review, advances in hydrophilic MOFs for N-linked glycopeptide enrichment are summarized. According to the synthesis strategies, those materials are categorized into three classes, namely pristine MOFs, MOFs with chemical modifications, and MOFs-derived composite. In each categorization, the preparation and the function of different moieties are covered, as well as the enrichment performances of sensitivity, selectivity, and practical application. Finally, a summary and future perspective on the applications of hydrophilic MOFs for N-linked glycopeptide enrichment are briefly discussed. This review is expected to raise awareness of the properties of hydrophilic MOFs and offer some valuable information to further research in glycoproteomics.